2007
DOI: 10.1210/jc.2006-1249
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Binding Protein-4 Levels and Clinical Features of Type 2 Diabetes Patients

Abstract: The current study shows that RBP4 is associated with variables related to insulin resistance and diabetic complications. The addition of pioglitazone for 12 wk to other diabetic medications the patients were already taking did not affect serum RBP4 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
176
6
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(206 citation statements)
references
References 23 publications
23
176
6
1
Order By: Relevance
“…Cho et al (6) found significantly different RBP-4 levels between patients with normal glucose tolerance on one hand and IGT and diabetes on the other hand. A similar increase in serum RBP-4 concentrations in diabetic subjects is observed in an independent study (25). Different patient characteristics might explain the differences observed in the association between RBP-4 and metabolic parameters.…”
Section: Univariate and Multivariate Correlationssupporting
confidence: 83%
“…Cho et al (6) found significantly different RBP-4 levels between patients with normal glucose tolerance on one hand and IGT and diabetes on the other hand. A similar increase in serum RBP-4 concentrations in diabetic subjects is observed in an independent study (25). Different patient characteristics might explain the differences observed in the association between RBP-4 and metabolic parameters.…”
Section: Univariate and Multivariate Correlationssupporting
confidence: 83%
“…On the contrary, higher levels of circulating RBP4 are described in men (35,37,65,67,72). This dimorphism was, however, not shown in all studies (32,73,84,85). Recently, higher RBP4 mRNA expression in adipose tissue was found in women when compared with men; this was, however, not reflected in the circulating levels (73).…”
Section: Sex-specific Dimorphism Of Rbp4mentioning
confidence: 88%
“…They showed that serum RBP4 levels were elevated in GLUT4 glucose transporter knockout mice and humans with obesity and type 2 diabetes [11]. Currently, increasing evidence denotes an association between increased circulating levels of RBP4 with type 2 diabetes mellitus and/or insulin resistance states [11,25,12,[26][27][28][29][30][31]. A pathophysiological link between RBP4 and type 2 diabetes mellitus may also arise from impaired insulin secretion [3].…”
Section: Discussionmentioning
confidence: 99%